Effect of Soil Texture on Soil Infiltration Rate - O. P. Folorunso; J. O. Aribisala (Archives of Current Research International, 2018)
The process of infiltration may be quite complex due to non-uniformity of the initial moisture content and soil properties and it is a process governed by force of gravity and capillary action. This process affects surface runoff, soil erosion, and groundwater recharge. It is important therefore to measure the rate of infiltration to balance the ecosystem. This work assesses the performance of a locally fabricated double-ring infiltrometer for infiltration rate measurement using selected locations within the Ekiti State University, Nigeria. The double-ring infiltrometer test is a well-recognized and documented technique for directly measuring soil infiltration rate. From the observation of the study, the soil location can be texturally classified as sandy clay, the infiltration depths obtained from the double ring infiltrometer test are 0.97t1.22 ─ 2.9 and 0.25t1.22 ─ 2.0. The result demonstrates that the intake rate of soil depends on the texture of soil, surface condition of the soil and time of pounding.